On the art of doing surveys among adolescents. (30th September 2020) - Due, P; Arnarsson, A M; Lyyra, N; Löfstedt, P; Madsen, K R; Thorsteinsson, E B; Välimaa, R; Torsheim, T; Damsgaard, M T; Eriksson, C
Abstract: The aim is to discuss methodological challenges for research on adolescent positive mental health. A first consideration is which questions should the measurement instrument answer. In the clinical context it should have the properties of giving enough information for making a diagnosis of high quality. In the public health context, its objective may be to give information that enables the researcher to describe trends at the population level and provide guidance on areas of intervention. The HBSC study is monitoring the health and health behaviour of school-aged children in a public health context. It is a population survey, defined by the form of data collection and the method of analysis. The data is collected by questionnaire from a representative sample of school-aged children. It tries to answer descriptive questions (What, who, when?), but also tries to explore causal associations (Why?), given the limitations of the cross-sectional design. Surveys have advantages: Good for gathering descriptive data; Can cover a wide range of topics. Are relatively inexpensive to use; Can include large number of respondents; and Can be analysed using a variety of existing software. Among the disadvantages can be mentioned: Self-report may lead to biased reporting; Data may provide a general picture but lack depth; Difficult to obtain adequate information on context; and Differences in understanding: it is difficult to formulate questions in such a way that it will mean exactly same thing to each respondent. The choice of measurement tools or indicators involves both theoretical and practical issues. Multidisciplinary research teams may include different theoretical traditions, which is an asset but also make it necessary to be explicit regarding overall aims of the study. Most often the theoretical issues focus one of three topics: the value of the types of data; the relative scientific rigor of the data; or basic, underlying philosophies of evaluation.